The effect of rate of injection on injection pressure profiles measured using in‐line and needle‐tip sensors: an in‐vitro study. (22nd August 2018) - Saporito, A.; Quadri, C.; Kloth, N.; Capdevila, X.
Summary: Alongside ultrasonic visualisation, measurement of injection pressure is an effective tool for reducing the risk of intraneural injection during peripheral nerve block. The aim of this study was to compare injection pressure profiles when measured along the injection line with the pressure measured directly at the needle tip using different rates of injection. A syringe pump delivered a 5‐ml injection of saline into silicone gel at three different speeds (5 ml.min −1, 10 ml.min −1 and 15 ml.min −1 ). Fibreoptic pressure sensors recorded real‐time pressure profiles of the injection pressure directly at the needle tip and along the injection line. A total of 15 injections were successfully performed, five for each injection rate, totalling 30 recorded pressure profiles. More rapid rates of injection caused peak pressure measured in‐line to increase, whereas pressure measured at the needle tip remained constant (mean (SD) pressure in‐line 30.76 (3.45) kPa vs. 72.25 (1.55) kPa and mean (SD) pressure at needle tip 19.92 (1.22) kPa vs. 20.93 (2.66) kPa at 5 ml.min −1 and 15 ml.min −1, respectively). Injection pressure profiles showed that in‐line pressure measurement failed to record precise real‐time pressure changes occurring at the needle tip (mean (95%CI) pressure difference 10.8 (6.98–14.70) kPa vs. 51.2 (47.52–54.89) kPa for in‐line and needle‐tip measures, respectively). We conclude that, in order to accurately monitor the true injection pressure generated, independent from operator and injection parameters, measurement at the needle tip is necessary, as injection pressure measured along the injection line is an unreliable surrogate. 개요: 초음파를 통한 시각화(visualisation)와 함께, 주입 압력 (injection pressure)의 측정은 말초신경 차단 중에 신경 내 주사(intraneural injection)의 위험을 줄이는데 효과적인 방 법이다. 본 연구는 다양한 주입 속도(injection rate)로 주사 하는 동안 주사선(injection line)을 따라 측정한 주사선 내 주입 압력 프로필(injection pressure profile)과 주삿바늘 끝 에서 직접 측정한 압력을 비교해 보고자 하였다. 주사기 펌프 를 사용하여 세 가지 속도(5 mL/min, 10 mL/min 및 15 mL/min)로 5‐mL의 식염수를 실리콘 겔 속으로 주사하였다. 광섬유 압력 감 지기를 사용하여 주입 압력의 실시간 압력 프로필을 주사선 을 따라 주사선 내(in‐line sensor)에서, 그리고 주삿바늘 끝 (needle‐tip sensor)에서 직접 측정, 기록하였다. 각 주입 속 도당 5회씩, 총 15회의 주사가 성공적으로 수행되었으며, 총 30개의 압력 프로필이 기록되었다. 보다 빠른 주입 속도에서 주사선 내에서 측정된 최고 압력(peak pressure)이 증가한 반면, 주삿바늘 끝에서 측정된 압력은 일정하게 유지되었다 (각각 5 mL/min vs. 15 mL/min의 속도에서 주사선 내에서 측정된 압력의 평균 [표준편차]: 30.76 [3.45] kPa vs. 72.25 [1.55] kPa, 주삿바늘 끝에서 측정된 압력의 평균 [표준편차]: 19.92 [1.22] kPa vs. 20.93 [2.66] kPa). 주입 압력 프로필 결 과상 주사선 내 압력 측정이 주삿바늘 끝에서 발생하는 실시 간 압력 변화를 정확하게 반영하지 못하였다(각각 5 mL/min vs. 15 mL/min의 속도에서 주사선 내 측정과 주삿바늘 끝 측정 간의 압력 차이의 평균 [95%CI]: 10.8 [6.98‐14.70] kPa vs. 51.2 [47.52‐54.89] kPa). 결론적으로 주사선을 따라 측정 된 주입 압력은 신뢰할 수 없는 대리변수이기 때문에 주사할 때 생성되는 실제 주입 압력을 시술자 및 주입 매개변수들과 관련없이 정확하게 감시하기 위해서는 주삿바늘 끝에서의 측 정이 필요하다.